34.5k views
1 vote
If f(x) = 4^x - 8 and g(x) = 5x + 6, find (f - g)(x)

2 Answers

4 votes

Answer:


4^x-5x-14

Explanation:


f-g=(4^x-8)-(5x+6)=4^x-8-5x-6=4^x-5x-14

User Sdive
by
5.9k points
5 votes

Answer:

The value of
(f-g)(x)=4^x-5x-14

Explanation:

Given : If
f(x) = 4^x-8 and
g(x)=5x+6

To find : The value of
(f - g)(x)?

Solution :


f(x) = 4^x-8


g(x)=5x+6

We can write,
(f-g)(x)=f(x)-g(x)

Substitute the value of f(x) and g(x)


(f-g)(x)=4^x-8-(5x+6)


(f-g)(x)=4^x-8-5x-6


(f-g)(x)=4^x-5x-14

Therefore, The value of
(f-g)(x)=4^x-5x-14

User Verec
by
5.8k points